Perancangan Sistem Informasi Manajemen Biaya Proyek Menggunakan Metode Earned Value Management pada PT. Kaltacitra Utama Berbasis Web - Syahputra, Dandy; Zulkarnain, Iskandar; Ramos, Samuel (Eksplorasi Teknologi Enterprise dan Sistem Informasi (EKSTENSI), 2023)
The effectiveness of project cost management has become a primary concern in the construction industry. Traditional constraints in project cost monitoring necessitate a solution to enhance efficiency, transparency, and accuracy in management. This research aims to introduce a web-based project cost management information system that focuses on the application of the Earned Value Management (EVM) method. By employing a web-based system development approach using the Earned Value Management (EVM) method to accurately monitor project costs and performance. The utilization of web technology enables real-time access for stakeholders, facilitating more timely monitoring and evaluation. The implementation of this system has made a positive contribution to project cost management at PT. Kalta Citra Utama. Testing conducted demonstrates increased real-time transparency and accuracy in project cost information, providing better support for managerial decision-making. Implementing a web-based project cost management information system with the Earned Value Management (EVM) method at PT. Kalta Citra Utama will prove to enhance the efficiency and accuracy of project cost management. This demonstrates significant potential in optimizing project management practices in the construction industry.